The Influence of Social Media Marketing, Brand Associations, Perceived Quality, Brand Awareness And Brand Loyalty Towards Brand Equity And Brand Image As Mediation Variable - Dion Dewa Barata; . Susanti (Inovbiz: Jurnal Inovasi Bisnis, 2022)
In the consumer market, there are so many unidentified consumers that it is difficult for companies to build personal relationships with each customer (Tjahyadi Arlan, 2010). One of the most important ways that can be taken by marketers to build personal relationships with customers is through a symbol, namely a brand. This research aims to analyze the influence of social media marketing, brand associations, brand associations, perceived quality, brand awareness and brand loyalty towards brand equity and brand image as mediation variables. In order to analyze this research question, the author uses six hypotheses that will be examined. This research using his research is categorized as causal-comparative research, which is research that involves measuring variables and examining relationships between variables on patterns, correlations, or causal relationships. The variables in this study are brand association, perceived quality, brand awareness and brand loyalty to brand equity and brand image as mediating variables.Â  The sampling method used is simple random sampling, which is a sampling technique by providing equal opportunities for each member of the population to become the research sample. The variables in this research consisted of 3 types of variables, including: independent, intervening, and dependent. The result of this research found that from six hypotheses, 5 of them are proven. It found that brand associate, perceived quality, brand awareness, brand loyalty, and brand image have a positive impact towards brand equity. However, there is no significant impact of social media marketing towards brand equity.Â Keywords: Brand Associations, Brand Awareness, Brand Equity, Brand Image, Brand Loyalty, Social media marketing